Promoting Students’ Vocabulary Mastery by Using Flashcards - Maureen, Gabby; Rahmansyah, Habib (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
There is a problem with students' limited vocabulary, especially for EFL students. Vocabulary instruction through instructional media is one of the factors contributing to the issue. This study has aims to find out: 1) How the implementation of flashcard in teaching vocabulary, 2) How vocabulary is mastered by EFL students both before and after using flashcard media; and 3) The impact of flashcard media on students’ vocabulary mastery. Pre-experimental design was used in a quantitative research methodology. There were 62 pupils in the population, and 31 individuals were selected for the sample using a systematic sampling procedure. The research instruments in this study were observation and multiple choice test. The research revealed that flashcard media brings a significant effect on students’ vocabulary mastery.